Painful Unilateral Knee Snapping after Hyperextension Injury and Meniscus Tear - Karsen, Phillip; Brinkman, Joseph; Day, Jonathan; McGurren, Daniel; Patel, Karan (The Surgery Journal, 2023)
This case involves a healthy male with painful lateral knee pain and snapping after a hyperextension injury. Initially, this was felt to be from a displaced lateral meniscus tear; however, he failed to improve after meniscal debridement. Further workup with an ultrasound and magnetic resonance imaging identified an aberrant biceps femoris anatomy. He was taken to the operating room and the aberrant slip was identified. A tenodesis of the aberrant slip to the biceps femoris was completed. This resolved the patient's pain and snapping, and he was able to return to all activities.
Keywords: biceps femoris; snapping; lateral knee pain